1997
DOI: 10.1104/pp.115.2.737
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene-Mediated Programmed Cell Death during Maize Endosperm Development of Wild-Type and shrunken2 Genotypes

Abstract: We characterized the progression of programmed cell death during maize (Zea mays L.) endosperm development of starchy (Su; wild-type) and shrunken2 (sh2) genotypes and tested the involvement of ethylene in mediating this process. Histological and viability staining demonstrated that endosperm cell death was initiated earlier and progressed more rapidly in sh2 endosperm compared with Su endosperm. lnternucleosomal DNA fragmentation accompanied endosperm cell death and occurred more extensively in sh2 endosperm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
179
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(189 citation statements)
references
References 56 publications
8
179
1
1
Order By: Relevance
“…5 Previous studies of maize and barley have revealed that starch first is deposited in the central endosperm and then spreads toward the periphery during development, 6,39 and endosperm cell death closely follows the pattern of starch deposition in maize. 6 We revealed that the developing rice endosperm displays a pattern of starch accumulation and cell death similar to that in barley and maize. This finding suggests that a common position cue may specify the fate of starchy endosperm cells during development, at least in rice, maize, and barley.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Previous studies of maize and barley have revealed that starch first is deposited in the central endosperm and then spreads toward the periphery during development, 6,39 and endosperm cell death closely follows the pattern of starch deposition in maize. 6 We revealed that the developing rice endosperm displays a pattern of starch accumulation and cell death similar to that in barley and maize. This finding suggests that a common position cue may specify the fate of starchy endosperm cells during development, at least in rice, maize, and barley.…”
Section: Discussionmentioning
confidence: 99%
“…To assess the endosperm cell viability, cross sections located at the longitudinal median of the endosperm were stained by Evans blue as described previously. 6 At least 20 caryopses were observed at each stage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some plant PCD programs induce chromatin condensation and fragmentation of nuclear DNA into a nucleosomal ladder [18][19][20][21], little is known about intracellular components and mechanisms involved in these events in plants. In animal cells, each apoptotic endonuclease such as CAD/DFF40, endoG and DNase II is solely capable of inducing DNA laddering and/or chromatin condensation [10][11][12][13]15].…”
Section: Requirement Of a Heat-labile Molecule(s) In Apoptoticmentioning
confidence: 99%
“…Several apoptogenic effectors, such as caspases (cysteine proteases) [9][10][11][12], CAD/DFF40 (caspase-activated DNase/40 kDa DNA fragmentation factor) [9][10][11][12], endoG (mitochondrial endonuclease G) [13], DNase I [14], DNase II [15], AIF (apoptosis-inducing factor) [16] and Acinus (apoptosis chromatin condensation inducer in the nucleus) [17], have been implicated in mediating these nuclear disintegration processes using a cell-free system. In plants, chromatin condensation and DNA laddering are induced during PCD in response to biotic/abiotic stresses and developmental factors [4,6,[18][19][20][21][22]. However, only limited information is available about plant effectors, especially those involved in the executive phase of plant PCD.…”
Section: Introductionmentioning
confidence: 99%